2014
DOI: 10.1093/brain/awu024
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry and heterogeneity of Alzheimer’s and frontotemporal pathology in primary progressive aphasia

Abstract: Fifty-eight autopsies of patients with primary progressive aphasia are reported. Twenty-three of these were previously described (Mesulam et al., 2008) but had their neuropathological diagnoses updated to fit current criteria. Thirty-five of the cases are new. Their clinical classification was guided as closely as possible by the 2011 consensus guidelines (Gorno-Tempini et al., 2011). Tissue diagnoses included Alzheimer's disease in 45% and frontotemporal lobar degeneration (FTLD) in the others, with an approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

31
361
5
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 296 publications
(401 citation statements)
references
References 60 publications
(99 reference statements)
31
361
5
4
Order By: Relevance
“…At the Northwestern Alzheimer's Disease Brain Bank, 26% of the control population (n 5 190) has at least one e4 allele, whereas this frequency increases to 59% in those with an amnestic dementia during life and AD at autopsy (n 5 75). 1 The 27% frequency of e4 allele carriers in the 19 PPA participants with biomarker evidence or autopsy-confirmed AD reported in the current investigation is similar to control values. These data are consistent with previous reports 23,24 suggesting the e4 allele of APOE is not a risk factor for clinical PPA or AD pathology in PPA.…”
Section: 13supporting
confidence: 84%
See 3 more Smart Citations
“…At the Northwestern Alzheimer's Disease Brain Bank, 26% of the control population (n 5 190) has at least one e4 allele, whereas this frequency increases to 59% in those with an amnestic dementia during life and AD at autopsy (n 5 75). 1 The 27% frequency of e4 allele carriers in the 19 PPA participants with biomarker evidence or autopsy-confirmed AD reported in the current investigation is similar to control values. These data are consistent with previous reports 23,24 suggesting the e4 allele of APOE is not a risk factor for clinical PPA or AD pathology in PPA.…”
Section: 13supporting
confidence: 84%
“…These proportions are in line with those of an autopsy series of 58 PPA cases examined at various severity stages, in which 69% of all cases with AD pathology as the primary diagnosis had logopenic aphasia. 1 These results seem at odds with another study, also of PPA participants with autopsy or biomarker evidence of AD, where a complete overlap with PPA-L was reported. 25 However, in that study, grammatical ability was not reported and 5/14 participants presented with additional nonverbal memory impairments.…”
Section: 13mentioning
confidence: 83%
See 2 more Smart Citations
“…This is a novel report of PPA secondary to DLS. Previous clinicopathologic correlates of PPA have reported 9 underlying pathologies, including Alzheimer pathology; frontotemporal lobar degeneration (FTLD)-tau of the corticobasal degeneration type, progressive supranuclear palsy type, and Pick type; FTLD-TDP types A, B, and C; mixed AD and dementia with Lewy body pathology 6 ; and sporadic Creutzfeldt-Jakob disease. 7 The hemispheric asymmetry is the common denominator for neuropathologic entities underlying PPA.…”
mentioning
confidence: 99%